Design and Performance Measurement of a Miniaturized Implantable PIFA Antenna for Biomedical Applications - Islam, Nasim Al; Arifin, Farhadur (AIUB Journal of Science and Engineering (AJSE), 2017)
An implantable PIFA (Planar Inverted F Antenna) antenna for biomedical applications is proposed in this study. The main notability of this design refers to its subtle dimension, flexibility and subordinate thickness that makes it perfectly suitable for implementing inside human or animal tissues for Wireless Body Area Networks (WBAN). The antenna is aimed to operate in the Industrial, Scientific and Medical (ISM) band (2.4 2.4835 GHz). The thickness of this antenna is only 0.735 mm, which implies that this antenna is suitable to perform under bent conditions. The antenna offers a compact design with a dimension of 9.48 mm × 7.8 mm × .735 mm (54.348 mm3). Copper and Rogers R03010 are chosen as the patch material and substrate material accordingly. The antenna is encapsulated inside biocompatible material Rogers R03010 for safety concern inside skin or muscle tissues. Several types of analysis and performance measurement of this antenna have been done by using CST Microwave studio in both planar and bent conditions by maintaining the electrical properties of human skin tissues. Specific Absorption Rate (SAR) and thermal loss are evaluated to comply with the antenna safety issues. For proving biocompatibility and versatility of this antenna, performance analysis by changing different patch materials and substrate materials have been done after putting the antenna inside different human tissue models. Finally, the antenna is fabricated on to a FR4 substrate and its performance is measured using Agilent Technologies E5071C Network Analyzer.